Preface - Ziemiański, Leon; Waszczyszyn, Zenon (Computer Assisted Methods in Engineering and Science, 2011)
This Special Issue contains papers related to the Special Sessions on Artificial Neural Networks (ANNs) in Civil Engineering, organized at the 57th Annual Conference on Scientific Problems of Civil Engineering (CE). The conference called for short Krynica 2011 was organized by the Rzeszów University of Technology under the auspices of the Committee of Civil Engineering of the Polish Academy of Sciences and the Polish Association of Civil Engineers and Technicians. The Special Issue I contains seven papers. The first paper has the state-of-the-art character. It concerns especially the short discussion of the most important achievements presented at the Special Session of the 57th Annual Conference Krynica 2011. The next three papers deal with applications of ANNs in various fields of civil engineering. They concern the analysis of building response for paraseismic excitations, applications if various ANNs in geodesy and structure element diagnosis. Then two papers are devoted to the development of hybrid computational systems corresponding to the updating of simple steel structures and reliability analysis of more complex engineering structures. The last paper deals with the application of the Recurrent Cascade Neural Network in an inverse analysis problem of predicting of a small additional mass location at a steel plate.